Entendimento sistêmico dos processos de negócios: uma abordagem exploratória - Librelato, Tatiane Pereira (Universidade do Vale do Rio dos Sinos, 2012)
From the perspective of business processes, the companies invest in innovations and improvements, where usually established approaches are applied. This dynamic starts by a diagnostic modeling, or not, the business processes for understanding the current situation. However, such approaches usually do not consider the circularity of the interrelationships of the systems of the organization and how these connections affect the systems between systems. Regarding the paradigm of Business Process Improvement, think of changes without thinking in the elements inherent to human perception can facilitate the decision-making in these possibly present to unexpected problems in the future, interfering in business processes as a whole. Thus, this research aims to propose an approach to systemically understand business processes through the integration between the Business Process Engineering (BPE) and Systems Thinking. Then were combined the concepts of such areas concerning the aims of research with the Systems Method. An initial approach was structured and applied in exploratory case study with single unit of analysis. From the empirical evaluation approach was refined in the case, so a search of applied nature and qualitative approach. The search results are evidence that the combination between BPE and ST can contribute to better understanding of business processes.
Keywords: Engenharia de processos de negócios; Pensamento sistêmico; Método sistêmico; Business process engineering; System thinking; System method; ACCNPQ::Engenharias::Engenharia de Produção